Inclusive growth in India : agriculture, poverty, and human development - Mahendra Dev, S. (Oxford, 2007)
The volume emphasizes the need for economic reforms with equitable development. It focuses on key inter-related elements of inclusive growth: agriculture, poverty, food security and employment, social sector, and regional disparities; examining the performance, issues and challenges. Arguing for pro-poor and people-centric policies, it suggests that growth and equity objectives should be pursued simultaneously. It also stresses the importance of women's economic and social empowerment and upliftment of socially disadvantaged sections for realizing the objective of inclusive growth.